Comparison of step-by-step kinematics in repeated 30-m sprints in female soccer players - van den Tillaar, R. (The Journal of Strength and Conditioning Research, 2018)
The aim of this study was to compare kinematics in repeated 30-m sprints in female soccer players. Seventeen subjects performed seven 30-m sprints every 30 seconds in one session. Kinematics was measured with an infrared contact mat and laser gun, and running times with an electronic timing device. The main findings were that sprint times increased in the repeated-sprint ability test. The main changes in kinematics during the repeated-sprint ability test were increased contact time and decreased step frequency, whereas no change in step length was observed. The step velocity increased in almost each step until the 14th, which occurred around 22 m. After this, the velocity was stable until the last step, when it decreased. This increase in step velocity was mainly caused by the increased step length and decreased contact times. It was concluded that the fatigue induced in repeated 30-m sprints in female soccer players resulted in decreased step frequency and increased contact time. Using this approach in combination with a laser gun and infrared mat for 30 m makes it very easy to analyze running kinematics in repeated sprints in training. This extra information gives the athlete, coach, and sports scientist the opportunity to give more detailed feedback and helps to target these changes in kinematics better to enhance repeated-sprint performance.